SHORT-TERM COMPLICATIONS OF TRANSURETHRAL RESECTION OF THE PROSTATE PERFORMED BY UROLOGY RESIDENT IN EDUCATIONAL HOSPITAL: CHARACTERISTICS AND DETERMINANT FACTORS - Daryanto, Besut; Budaya, Taufiq Nur; Meiyanto, Johanes Dwi (Indonesian Journal of Urology, 2024)
Objective: This research wanted to figure out the characteristics and determinant factors of short-term complications of TURP performed by urology resident in educational hospital. Material & Methods: This study was an analytical study using secondary data from electronic medical records of the total sample of 502 BPH patients undergoing TURP performed by urology resident January from 2015 until June 2022, and evaluated short-term complications, Clavien Dindo, and level of urology resident. Inclusion were BPH patients undergoing TURP by urology resident, while the criteria of exclusion were incomplete data of patient’s demographic and records of clinical data. Results were displayed descriptively in distribution tables and analyzed using logistic regression with STATA 17. Results: Short-term complications of TURP were found in 10 patients (1.99%), i.e., bleeding (0.79%), clot retention (0.6%), and urinary retention (0.6%). The commonest groups were age at 61-70 (0.79%), Clavien Dindo I (0.79%), urology resident level at 5th semester (0.99%), prostate volume >50cc (0.99%) and complaint of urinary retention (0.99%). There were no significant correlations between patient age, level of urology resident, prostate volume, and chief complaint compared to rate of complication (p>0.25). Conclusion: TURP remained surgery of choice for BPH despite several short-term complications performed by different level of urology resident and there were no significant correlations between level of urology resident and rate of complication. Keywords: BPH, Urology Resident, Short-Term Complications of TURP, Clavien Dindo.